2022
DOI: 10.1038/s41586-022-05110-4
|View full text |Cite
|
Sign up to set email alerts
|

Divergent genomic trajectories predate the origin of animals and fungi

Abstract: Animals and fungi have radically distinct morphologies, yet both evolved within the same eukaryotic supergroup: Opisthokonta1,2. Here we reconstructed the trajectory of genetic changes that accompanied the origin of Metazoa and Fungi since the divergence of Opisthokonta with a dataset that includes four novel genomes from crucial positions in the Opisthokonta phylogeny. We show that animals arose only after the accumulation of genes functionally important for their multicellularity, a tendency that began in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 73 publications
13
44
0
Order By: Relevance
“…Taken together, our analyses revealed that early-diverging fungi possess a large number of HGs shared specifically with protists, and that these were gradually lost during evolution. The broad conservation of protist HGs may explain the morphological and genetic similarities between EDF and protists reported in previous studies 16,23,24,31,32 and also clarifies why the genome content of fungi reflects that of ancestral opisthokonts more than metazoan gene content does 33 . However, our data revealed that the retention of protist genes is not restricted to certain gene families, but is a genomewide trend in early-diverging fungi.…”
Section: Gradual Turnover Of Protist Heritage and Synapomorphies In F...supporting
confidence: 65%
See 1 more Smart Citation
“…Taken together, our analyses revealed that early-diverging fungi possess a large number of HGs shared specifically with protists, and that these were gradually lost during evolution. The broad conservation of protist HGs may explain the morphological and genetic similarities between EDF and protists reported in previous studies 16,23,24,31,32 and also clarifies why the genome content of fungi reflects that of ancestral opisthokonts more than metazoan gene content does 33 . However, our data revealed that the retention of protist genes is not restricted to certain gene families, but is a genomewide trend in early-diverging fungi.…”
Section: Gradual Turnover Of Protist Heritage and Synapomorphies In F...supporting
confidence: 65%
“…We think this explains why EDF gravitate towards protists in gene content-based analyses (See Fig. 1) and provides a genomewide explanation for sporadic evidence for the similarity of EDFs to protists from analyses of single genes 24,25 , individual genomes 33 or TF-omes 45 . At the same time, we detected a limited number of gene families that could be considered synapomorphic for fungi, in agreement with previous conjectures on the lack of synapomorphies in the kingdom 11,22 .…”
Section: Discussionmentioning
confidence: 81%
“…Similarly in plants, the genetic basis for symbiont perception, nodule organogenesis and nitrogen-fixation genes already existed in the common ancestor of nitrogen-fixing legumes, and diversified in downstream nitrogen-fixing lineages (Libourel et al, 2022). Such macroevolutionary transitions punctuate the eukaryotic tree of life, where the acquisition of new molecular functions accompanies major evolutionary and ecological transitions, but precedes divergence and lifestyle specialisation in downstream lineages (Domazet-Lošo et al, 2022; Ocana-Pallares et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In none of the GH99 sequences from CRuMS (4 taxa sampled) Y189 was present, but a significant proportion (4 sequences, 27%) of hits from Amoebozoa have this feature (Supplementary File S11). Within Obazoa, a sister clade to Amoebozoa, only Opisthokonta retained Y189 and among the opisthokonts, the only nucletmycean that contains it is the recently sequenced Parvularia atlantis 46 . No true fungi possess the GH99 domain.…”
Section: Resultsmentioning
confidence: 99%